ANALISIS KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH - admin; Suci, Jihan (JURNAL KEBANGSAAN, 2021)
Hotel tax is one source of Local Owned Revenue of Lhokseumawe district, but in terms of contribution, hotel taxes have coustraints in tapping the PAD, that is still the tax payer has not fullfilled the obligation to pay the taxes. Another problem that has to be faced is gap between budgeting and the realization of hotel tax acceptance in 2015 until 2018. It caused the small number of hotel tax contribution of Lhokseumawe district. The purpose of this study is to know the contribution of hotel tax to PAD in Lhokseumawe district. Qualitative method is used in this study. The result of study indicates that hotel tax contribution in 2015-2018 was not always incerasing or experience the fluctuation, where the presentage of the greatest contribution of hotel tax occured in 2018 was 0,061 % and the lowest a presentage in 2015 was 0,023 % with contribution average 0,036 %. Local government should increase the potential and the sources local owned revenue especially hotel tax acceptance. There will this increase the tax acceptance.